2013
DOI: 10.1177/1708538113516322
|View full text |Cite
|
Sign up to set email alerts
|

Temporal artery biopsy size does not matter

Abstract: This study aimed to clarify whether positive temporal artery biopsies had a greater sample length than negative biopsies in temporal arteritis. It has been suggested that biopsy length should be at least 1 cm to improve diagnostic accuracy. A retrospective review of 149 patients who had 151 temporal artery biopsies was conducted. Twenty biopsies were positive (13.3%), 124 negative (82.1%) and seven samples were insufficient (4.6%). There was no clinically significant difference in the mean biopsy size between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…29 There have been various conflicting perspectives in the literature advocating for longer biopsies, 25,26 and others finding that the mean TAB lengths were not significantly different between positive and negative results. 22,30 Considering that our study showed a statistically significant increase in the positive diagnosis of GCA with longer TAB (Figs 1,2), we advocate the need for the resection of longer specimen on biopsies.…”
Section: Discussionmentioning
confidence: 68%
“…29 There have been various conflicting perspectives in the literature advocating for longer biopsies, 25,26 and others finding that the mean TAB lengths were not significantly different between positive and negative results. 22,30 Considering that our study showed a statistically significant increase in the positive diagnosis of GCA with longer TAB (Figs 1,2), we advocate the need for the resection of longer specimen on biopsies.…”
Section: Discussionmentioning
confidence: 68%
“…However, to this day, there is no unanimous consensus regarding the optimal length of biopsy, and the literature reveals a wide range of lengths considered adequate from 5 to 50 mm. 4,10,[18][19][20][21][22][23][25][26][27][28][29] Taylor-Gjevre and colleagues postulated that a threshold length of 10 mm post-formalin fixed arterial segment was associated with increased diagnostic yield of GCA. 10 These authors recommended a minimum STAB length of 15 mm to allow for tissue shrinkage during fixation, which was estimated to be approximately 10%.…”
Section: Discussionmentioning
confidence: 99%
“…However, to this day, there is no unanimous consensus regarding the optimal length of biopsy, and the literature reveals a wide range of lengths considered adequate from 5 to 50 mm . Taylor‐Gjevre and colleagues postulated that a threshold length of 10 mm post‐formalin fixed arterial segment was associated with increased diagnostic yield of GCA .…”
Section: Discussionmentioning
confidence: 99%
“…52 By contrast, another study of 151 biopsies from 149 patients yielded 20 positive biopsies (13.3%), and there was no difference in the length of positive (mean 0.7 cm) compared with negative (mean 0.65 cm) biopsies. 53 The British Society for Rheumatology (BSR) guidelines recommend between a 1-and 2-cm length of artery to provide an adequate specimen, usually from only the symptomatic or most symptomatic side. 5 The presence of inflammatory infiltrates in the vasa vasorum was reported in 6.5% of 354 biopsies considered positive in one large study of patients with clinical features of GCA.…”
Section: Diagnosis Of Giant Cell Arteritis Relying On a Gold Standardmentioning
confidence: 99%
“…5 However, other studies have suggested that 0.7 cm is an adequate length; 52 in fact, even smaller biopsies might be adequate, with no evidence of a difference in positive biopsies for samples < 0.65 cm compared with those longer than 0.7 cm. 53 The biopsy length referred to in the current study is the measurement taken by the pathologists once a specimen arrives in the laboratory. It is known that shrinkage occurs once the specimen has been excised; we did not measure the length of the specimen obtained by surgeons at the time of sampling.…”
Section: Generalisability Of Current Findingsmentioning
confidence: 99%